Intelligent stability margin improvement using series and shunt controllers - Mahdi Karami; Norman Mariun; Mohd Amran Mohd Radzi; Gohar Varamini (Institute of Advanced Engineering and Science, 2021)
Electric market always prefers to use full capacity of existing power system to control the costs. Flexible alternate current transmission system (FACTS) devices introduced by Electric Power Research Institute (EPRI) to increase the usable capacity of power system. Placement of FACTS controllers in power system is a critical issue to reach their maximum advantages. This article focused on the application of FACTS devices to increase the stability of power system using artificial intelligence. Five types of series and shunt FACTS controllers are considered in this study. Continuation power flow (CPF) analysis used to calculate the collapse point of power systems. Controlling parameters of FACTS devices including their locations are determined using real number representation based genetic algorithm (RNRGA) in order to improve the secure margin of operating condition of power system. The 14 and 118 buses IEEE standard test systems are utilized to verify the recommended method. The achieved results manifestly proved the effectiveness of proposed intelligent method to increase the stability of power system by determining the optimum location and size of each type of FACTS devices.